Relationship between Husband's Support and Compliance of Injecting Family Planning Adjunct Mothers in Doing Re-Injections in the Working Area of the Puuwatu Health Center - Sella Pratiwi; Mien Mien; Muhammad Syahwal; Narmi Narmi (KLASICS, 2023)
The acceptor's compliance in re-injecting contraception can be seen from the timeliness of re-injecting where if there is a delay in the acceptor's re-injection it will reduce the effectiveness of the contraception. The purpose of this study was to determine the relationship between husband's support and maternal adherence to injecting family planning acceptors in re-injecting in the Puuwatu Health Center Work Area.. Method. The type of research used is a quantitative study with a cross-sectional study method conducted at the Puuwatu Health Center in July involving a sample of 93 people. Sampling using simple random sampling technique. The data were analyzed using the chi square test. Results. The results showed that in compliance with the use of re-injection family planning, there were 45 people (48.4%) who were obedient and there were 48 people (51.6%) who did not comply and on the support of their husbands, there were 53 people (57%) who received support. both from husbands and the less fortunate as many as 40 people (43%). In addition, there is a significant relationship between husband's support and maternal adherence to injecting family planning acceptors in re-injecting in the Puuwatu Health Center Work Area (ρ value = 0.025). Discussion. For husbands to support mothers in the use of re-injection family planning .